EFFECTS OF METEOROLOGICAL VARIABLES ON Pinus caribaea GROWTH IN DIFFERENT AGES AT THE AMAZON REGION. - Miranda Lima de Lima, Gabriel; Sebastião Braga Gomes, Nei; Augusto da Cunha, Thiago; Figueiredo Filho, Afonso (Floresta, 2022)
This study compares the impact of five meteorological variables on the diametric growth of Pinus caribaea var. hondurensis Barrett & Golfari in Vilhena, Rondônia. One thousand nine hundred sixty-eight trees were evaluated and classified at different ages: 600 trees were one year old; 600 trees were two years old; 768 trees were 13 years. The diameter measurement at the soil level (SL) was conducted in young stands between one and two years old. In the stand with 13 years old, the diameter was measured at 1.3 m (DCH). Using a Pressler borer, 50 increment cores were removed at DCH to measure the tree rings in LINTAB™ 6. The diametric growth was evaluated through the Periodic Increment (PI) for young stands and Current Annual Increment (CAI) for adult stands. The following variables were considered: average temperature (°C), precipitation (mm), solar radiation (Kj m-²), real evapotranspiration (mm), and maximum relative humidity (%). The Pearson Correlation Coefficient (r) proposed by Callegari-Jacques and the coefficient of variation (CV%) were used to establish the relationship between growth and meteorological variables. For young stands, the variables with higher positive correlation were real evapotranspiration and maximum relative humidity. However, the variable with a higher positive correlation in adult stands was average temperature, demonstrating a strong correlation until the sixth year of the species.